2018
DOI: 10.11591/ijece.v8i5.pp3860-3865
|View full text |Cite
|
Sign up to set email alerts
|

Gamification for Elementary Mathematics Learning in Indonesia

Abstract: The purpose of this research is to combine multimedia elements and mathematics learning material to a mathematic learning interactive application. Research and design methodology that used is Game Development Life Cycle (GDLC) which consist of initiation, pre-production, production, testing and release. Content inside the game is made using gamification and expert system concept. The result of this research is an interactive learning game to support student to understand mathematic materials. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
1
23
0
3
Order By: Relevance
“…The explanation of the mathematics material is conveyed with a simple narrative which is integrated with the display of graphics, images, and audio can improve the concentration of students in learning the concepts presented. This result is relevant to other research conducted by Yogi Udjaja et al, In his research on e-learning learning media in the form of interactive games, it was found that learning media helps students to learn mathematics interactively and attractively and is assessed to be able to convey mathematical material easily so that it supports students understanding Mathematical material [21], it shows that learning with interactive media has a very effective impact in increasing self-confidence so that it is appropriate to be applied, this is because interactive media is able to support students when learning either directly or indirectly [22].…”
Section: Relevant Research On the Use Of E-learning Mediasupporting
confidence: 68%
“…The explanation of the mathematics material is conveyed with a simple narrative which is integrated with the display of graphics, images, and audio can improve the concentration of students in learning the concepts presented. This result is relevant to other research conducted by Yogi Udjaja et al, In his research on e-learning learning media in the form of interactive games, it was found that learning media helps students to learn mathematics interactively and attractively and is assessed to be able to convey mathematical material easily so that it supports students understanding Mathematical material [21], it shows that learning with interactive media has a very effective impact in increasing self-confidence so that it is appropriate to be applied, this is because interactive media is able to support students when learning either directly or indirectly [22].…”
Section: Relevant Research On the Use Of E-learning Mediasupporting
confidence: 68%
“…Based on previous research [4][5][6][7][8][9][10][11][12][13][14][15][16], game development methods always change dynamically as needed. Based on this, the proposed game development method was developed according to the needs and changing times of the dynamic game production (DGP).…”
Section: Propose Methodsmentioning
confidence: 99%
“…Aleem et al said the quality of game development is still immature because there are still very few activities in game research especially in post-production [3]. Based on research that has been done, making a game requires systematic investigation, where the games are made whether it is in accordance with the desires and needs of players [4].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the success of Flipped classroom learning students must focus on instructional videos and a consistent presence is needed in practicing the techniques shown in lecture videos and class learning. [24] Research on gamification has also been widely applied in several previous studies, Yogi Udjaja, Vincent Sadino Guizot dan Natalia Chandra in their research developing gamificationbased interactive learning games to support students understanding mathematical material, the purpose of this application is to help students to learn mathematics interactively and attractively and be used to convey mathematical material easily [28]. Andrey V. Kirillova in his research mentioned that gamification can help create a beneficial learning environment, ensure high involvement of all participants in the education process, significantly reduce the impact of adverse factors in learning.…”
Section: Fig 2 Kahoot and Socrative Application 33 Relevant Research On Using Flipped Classroom And Gamificationmentioning
confidence: 99%